Analysis of medical costs and associated factors among inpatients with sexually transmitted infections at Can Tho Dermatology Hospital, 2024 - 2025 - Hung, Nguyen Phuc; Huong, Vo Thi My; Vinh, Nguyen Phu; Minh, Tang Nghiep; Minh, Nguyen Thi Tuyet; Suol, Pham Thanh; Bo, Nguyen Van; Phuong, Huynh Thanh; My, Le Thi Hong (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Background: Sexually transmitted infections (STIs) pose a major global health challenge. In Vietnam, the rising incidence of syphilis and HIV in high-risk groups is increasing the demand for healthcare and associated costs. Objective: This study aimed to analyze healthcare costs and identify some associated factors among inpatients diagnosed with STIs at Can Tho Dermatology and Venereology Hospital during 2024 - 2025. Subjects and Methods: A cross-sectional descriptive study was conducted on 178 inpatients treated for STIs from December 2024 to June 2025. Data on demographic characteristics, clinical conditions, and cost components were collected and analyzed using SPSS with both descriptive and inferential statistics. Results: The average total cost per hospitalization was 4,831,540 VND. Direct medical costs accounted for 38.7%, direct non-medical costs for 7.2%, and indirect costs for 54.2%. Non-medical costs were mainly due to transportation (66.4%) and meals (33.6%), while indirect costs were attributed to income loss among caregivers (54.8%) and patients (45.2%). Statistical analysis indicated that income level, number of comorbidities, and treatment outcomes were significantly associated with overall treatment costs (p < 0.05). Conclusion: Indirect costs represent the largest financial burden for STI inpatients. The study recommends supportive policies, such as subsidies for transport and meals, and strategies to mitigate income loss, to alleviate this burden and improve access to care. However, the single-center design and reliance on self-reported data for certain costs are key limitations to consider.